The Kangaroo and the Dragon: Party Ideology and its Impacts on Australia’s Methods of International Governance with China as a Case Study - Bosnjak , Stjepan (Journal of Law and Governance, 2015)
Australia’s two main political groupings – the ALP and Coalition – represent two different methods of governance, based on their political ideologies. These differences extend to the external sphere. It is the overarching aim of states to gain power to pursue what they deem is in their national interests, though the definition and method of governance changes according to the party in power. Broadly, the Coalition prefers to focus on bilateral relationships in achieving its national interest, whereas the ALP focuses on achieving its national interest through multilateral settings. When in government, both sides puts the powers and resources of the state towards achieving their preferred method of governance, and neglecting the other. This paper will look at a history of post WWII Australian Prime Minister’s methods of governance and then finish by engaging in a discussion of Australia’s current issues with governance concerning its economic relationship with China.